(untitled) (Journal of Economic Research & Business Administration, 2026)
This study analyses the relationship between the development of the hospitality industry and the level of regional inequality in Kazakhstan. The aim of the study is to assess dynamic relationships, identify their nature and determine the directions of influence. The relevance of the topic is due to the need to understand the role of the tourism sector as an instrument of regional policy capable of both stimulating smoothing and exacerbating economic disparities. The study uses panel data analysis for the country for the period from 2001 to 2023. To assess the development of the hospitality industry, indicators such as the number of accommodation places, the number of visitors served, and the volume of investment in fixed capital in this sector are considered. The level of regional inequality is measured using the Gini coefficient and the coefficient of variation of gross regional product (GRP) per capita. The methodology includes descriptive statistical analysis to identify the main characteristics of the data, as well as econometric modelling. The Hausman test was used to select the most appropriate panel data model (with fixed or random effects). The results obtained will make it possible to assess how the development of the hospitality industry affects regional disparities and the depth of poverty. The results of the study showed that the development of tourism infrastructure has a statistically significant positive impact on the sustainable growth of regions, while high youth unemployment and poverty depth hinder the achievement of balanced development. In addition, inflationary processes have varying degrees of impact depending on regional characteristics. The findings underscore the need to integrate tourism into regional sustainable development strategies and to intensify employment programmes. The recommendations are aimed at shaping differentiated regional policies that contribute to reducing inequality and stimulating local economic growth through the hospitality industry. Keywords: hospitality industry, regional inequality, panel data, Gini coefficient, econometric analysis.